2010
DOI: 10.1080/03643107.2010.500948
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Leave a Job: The Role of Individual Factors, Job Tension, and Supervisory Support

Abstract: This study examined the role of individual and organizational factors on intention to leave the job using a sample of 176Maryland-chapter NASW social workers. Using hierarchical regression analysis, it was determined that lower income, higher job tension, and lower supervisory support are related to higher intention to leave. Gender moderates the relation between supervisory support and intention to leave: for women there is a smaller difference in intention to leave for low and high supervisory support, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
3
13
0
2
Order By: Relevance
“…At most, material interest serves as a control variable. For the few empirical studies that take material interest into account, the effects of material interest are mixed, with some studies finding a significant relationship between material interest and employee’s intentions to leave organizations (Dickinson & Perry, 2002; Fakunmoju et al., 2010; Kim & Stoner, 2008) and some failing to reach the same result (Cohen-Callow et al., 2009; Hopkins et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…At most, material interest serves as a control variable. For the few empirical studies that take material interest into account, the effects of material interest are mixed, with some studies finding a significant relationship between material interest and employee’s intentions to leave organizations (Dickinson & Perry, 2002; Fakunmoju et al., 2010; Kim & Stoner, 2008) and some failing to reach the same result (Cohen-Callow et al., 2009; Hopkins et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Negative organizational behavior attitudes arise in employees who are not supported by their supervisor (Ng and Feldman, 2012;Fakunmoju et al, 2010). Positive organizational behaviors consist in employees receiving supervisor support (Turgut, 2011;Goh et al, 2015;Stinglhamber and Vandenberghe, 2003).…”
Section: Supervisor Supportmentioning
confidence: 99%
“…These controls were used because there is research that has demonstrated connections between satisfaction with pay (Pakunmoju, Woodruff, Kim, LeFevre, & Hong, 2010) and turnover intention. Length of time worked at the institution, along with academic rank, represent to an employee an "investment" in the organization.…”
Section: Instrumentmentioning
confidence: 99%
“…Organizational change and mergers can also be related to employee turnover intention. An employee’s decision to leave a position is usually not spontaneous but results from a process that begins with thinking about leaving, or turnover intention (Fakunmoju, Woodruff, Kim, LeFevre, & Hong, 2010). A number of factors are known to be related to turnover intention.…”
Section: Effects On Employeesmentioning
confidence: 99%